Learning for sustainability: Adult transformative learning through sustainability and culturalism perspectives - Tarsilla Lehmann; Usha Iyer-Raniga; Kathleen Mahoney (Social Sciences and Humanities Open)
The role of education is to enable change for the better. Sustainability education relies on humanity to act urgently to deal with what may be argued as the most pressing need of the 21st century. Transformative adult learning has the potential to drive positive behaviour change to address complex and wicked global problems. Addressing the frequent question of how society will build and achieve sustainability change, this article utilises education as a means for meaningful and tangible sustainable change through learning for sustainability. Commonly known as ‘education for sustainability’ (EfS), the authors use the transformative learning (TL) process via embedded sustainability and cultural perspectives to demonstrate how learning through a sustainability and culturalism perspective can aid and enhance knowledge exchange. In parallel, this article presents an exploratory examination of how Collaborative Online International Learning (COIL) can broaden and deepen intercultural learning, foster ethical responsibility, and promote non-essentialist discourses, resulting in improved awareness and understanding, taking a holistic approach to a sustainable future. We argue that innovative teaching methods such as COIL with embedded sustainability and cultural perspectives as demonstrated from a New Zealand vocational education (VE) course utilising sustainability and culturalism perspectives can transform learning, encouraging ethical and culturally responsive practice in individuals. Utilising quantitative methods, this study finds tangible enhanced changes in participants' sustainability knowledge, as well as significant improvement to personal and interpersonal awareness associated with cultural engagement, discourse, and metanarrative. The results of this case study demonstrate adult TL as contributory to current and future sustainable change and are applicable, not only to VE contexts but in any adult learning context.